Beyond the Steppe Frontier : A History of the Sino-Russian Border - Urbansky, Sören (Book collections on Project MUSE., 2020)
"Over two thousand miles long, the boundary between Russia and China is the world's longest land border. Though sometimes considered a backwater, the border region was always of critical geopolitical importance and has a fascinating history. Not only did this border divide the two largest Eurasian empires, it was also the place where European and Asian civilizations met, where nomads and settled peoples mingled, where the imperial interests of Russia, China, and Japan clashed, and where both conflicts and gestures of friendship between the world's largest Communist regimes were staged. This book is a history of this border from the late nineteenth century until the fall of the Soviet Union. The border has undergone a remarkable transformation since the late nineteenth century. As late as the 1920s, Russian, Chinese, and native worlds were intricately interwoven in the region, and the frontier was barely regulated. By the end of the twentieth century, however, the two countries had succeeded in cutting kin, cultural, economic, and religious connections between the two sides through deportation, forced assimilation, and nationalist propaganda campaigns. Only with the collapse of the Soviet Union would China and Russia reopen the border, but even today the line between countries demarcates two distinct regions with remarkably different worldviews and cultures. Drawing on sources in seven languages, including extensive archival research, interviews, and oral histories, Urbansky stresses the significant role of the local population in supporting, or more often undermining, the two states' border-making efforts"--